2014
DOI: 10.1182/blood-2014-03-557298
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of autocrine sonic hedgehog signaling in human CD138+ myeloma cell survival and drug resistance

Abstract: Key Points CD138+ MM cells are a major source of SHH. Autocrine SHH enhances MM drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 46 publications
4
79
0
Order By: Relevance
“…Few studies have shown the deregulation of Hh signaling in the BM of hematologic malignancies by immunohistochemistry; high SHH protein levels, for example, have been described in the BM samples of patients with acute promyelocytic leukemia, AML and multiple myeloma. 9,10 This is the first time, to our knowledge, that an increase in Hh ligands has been described in the BM of MDS.…”
mentioning
confidence: 69%
“…Few studies have shown the deregulation of Hh signaling in the BM of hematologic malignancies by immunohistochemistry; high SHH protein levels, for example, have been described in the BM samples of patients with acute promyelocytic leukemia, AML and multiple myeloma. 9,10 This is the first time, to our knowledge, that an increase in Hh ligands has been described in the BM of MDS.…”
mentioning
confidence: 69%
“…4C). We continued to examine the basal levels of ABCG2 and BCL2 in GCSCs, since they are the downstream targets of hedgehog signaling participating in drug resistance [23,29]. The results showed that both ABCG2 and BCL2 were significantly increased in CD44 + /Musashi-1 + BGC-823 and SGC-7901 cells compared with CD44 − /Musashi-1 − cells (Fig.…”
Section: Gastric Cancer Stem Cells Expressing Cd44 + /Musashi-1 + Arementioning
confidence: 94%
“…In the presence of HH ligands, SMO is activated transducing the signal to the cytoplasm via canonical signaling of GLI proteins [20]. Aberrant activation of SHH signaling has been shown to play crucial roles in the development of drug resistance to chemotherapy in many cancers [21][22][23]. It has recently been shown that SHH signaling is also involved in the resistance of CD44 + gastric adenocarcinoma to chemotherapy [24].…”
Section: Introductionmentioning
confidence: 98%
“…Plasmids of pCMV-p300 and 8×GLI-BS luciferase reporter were prepared as described previously 12,13. p21 siRNA (sc-29427) and control siRNA were purchased from Santa Cruz Biotechnology (Dallas, TX, USA).…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%